The Role of Hospitals in Cervical Cancer Prevention - Susilawati, Susie; Ocviyanti, Dwiana (Indonesian Socety of Obstetrics and Gynecology, 2014)
Objective: To evaluate the role of hospitals in DKI Jakarta on primary and secondary cervical cancer prevention. Method: This was a survey conducted to 25 hospitals, chosen with simple random sampling from 109 hospitals in DKI Jakarta. Questionnaire used for interview contained statements regarding knowledge, attitude and behavior of 117 health care professionals along with identification of facility preparedness for cervical cancer prevention within those 25 hospitals. Result: The assessment of knowledge shows that all health care professionals (100%) knew that HPV vaccination is used as a primary prevention for cervical cancer. About 98.3% respondent knew HPV vaccine injected intramuscularly. As much as 91.5% of the respondent knew HPV vaccine is given three times either at month 0, 1, 6 or at month 0, 2, 6. About 71.8% respondent knew deltoid as site for vaccine injection. Most of health care professionals (99.1%) knew VIA (visual inspection with acetic acid) can be used for early detection of cervical cancer. About 76.9% respondent knew how to interpret positive VIA results and 60.7% respondent knew how to do VIA test. As much as 93.2% health care professional knew the purpose of Pap test and about 82.1% knew how to do it. From attitude aspect, most of health care professionals (96.6%) agreed in giving HPV vaccination. About 94% of them agreed to do VIA test and about 98.3% agreed in conducting Pap test. From behavioral aspect, most of the respondent (76.9%) offered HPV vaccination to their clients/patients and 62.4% respondent did HPV vaccination. VIA test was offered and conducted by 52.1% and 30.8% of them, respectively. About 86.3% respondent offered Pap test and 71.8% did the Pap test. As many as 75% of female health care professionals who meet the qualification already had a Pap test for themselves, but only 32.5% ever been vaccinated for HPV. From facility aspect, twenty hospitals (80%) in DKI Jakarta offered HPV vaccination with Pap test can be done in all of them. VIA test and colposcopy were only available in eleven (44%) and ten (40%) hospitals respectively. Conclusion: Most hospitals in DKI Jakarta have health care professionals with good knowledge and attitude in cervical cancer prevention. However, not many have shown expected behavior in the primary prevention. Most hospitals in DKI Jakarta provide facilities for HPV vaccination and Pap test, but only few have VIA facilities and colposcopy. Keywords: cervical cancer prevention, health care professional, hospital